(untitled) (Prudentia Iuris, 2020)
The article addresses the problem of the common good in the political society and the respect for the family and the rest of infrapolitical societies, in accordance with the natural law and the principle of subsidiarity. The ideas of Professor Bernardino Montejano, and others authors of the classical tradition of UCA Law School, are taken as main source.